2004
DOI: 10.3168/jds.s0022-0302(04)73169-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Native Pasture to the Sensory Properties of Ragusano Cheese

Abstract: Ragusano is a Protected Denomination of Origin cheese produced in the Hyblean area of Sicily. Sixteen samples of Ragusano cheese from two different treatments [pasture and total mixed ration (TMR)] were evaluated after 4 and 7 mo of aging. The color of the cheeses produced from milk of cows consuming fresh native pasture plants was much more yellow than cheeses from TMR fed cows (i.e., higher Hunter b value). This was due to transfer of beta-carotene and related compounds from the diet and demonstrated that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 10 publications
2
60
0
14
Order By: Relevance
“…Dentro de las características del queso fresco de la región de Toluca, que lo diferencian de otros tipos de quesos elaborados en otras regiones del país (3,13) , cuyas características son más apreciadas por los consumidores locales, son la textura blanda, el sabor suave y su consistencia húmeda, que brindan un gusto particular del tipo de queso y el sabor a otros platillos autóctonos de la zona (14,15) . El sabor dulce y lácteo del queso fresco es influido por los componentes propios de la leche, los cuales son afectados por el tipo de dieta y proporción de forrajes nativos, en los que se supone una variación en su contenido nutricional y dentro de otros la proporción de ácidos grasos en la leche (30,31) . En el proceso de elaboración del queso, la molienda, la adición de sal, la microbiota nativa de la leche y del medio, modifican la composición química y las condiciones reológicas de la pasta, contribuyendo a brindar las características de degustación distintivas del queso genuino de la región (2,12).…”
Section: Resultados Y Discusiónunclassified
“…Dentro de las características del queso fresco de la región de Toluca, que lo diferencian de otros tipos de quesos elaborados en otras regiones del país (3,13) , cuyas características son más apreciadas por los consumidores locales, son la textura blanda, el sabor suave y su consistencia húmeda, que brindan un gusto particular del tipo de queso y el sabor a otros platillos autóctonos de la zona (14,15) . El sabor dulce y lácteo del queso fresco es influido por los componentes propios de la leche, los cuales son afectados por el tipo de dieta y proporción de forrajes nativos, en los que se supone una variación en su contenido nutricional y dentro de otros la proporción de ácidos grasos en la leche (30,31) . En el proceso de elaboración del queso, la molienda, la adición de sal, la microbiota nativa de la leche y del medio, modifican la composición química y las condiciones reológicas de la pasta, contribuyendo a brindar las características de degustación distintivas del queso genuino de la región (2,12).…”
Section: Resultados Y Discusiónunclassified
“…not reported in other cheeses evaluated by gas chromatography-olfactometry) were detected in the Ragusano cheese that was made from milk by cows fed with native Sicilian pasture plants. Furthermore, sensory analysis by trained panelists confirmed the difference between the two experimental treatments [7]. This research demonstrated clearly that some unique odor-active compounds found in pasture plants can be transferred to the cheese and identified by human beings.…”
Section: The Influence Of Native Pasture On the Aroma And Sensory Promentioning
confidence: 57%
“…As reported by Carpino et al (2004), cheese yellow index, related to carotenoids content, resulted higher in Ragusano produced from cows fed with natural pasture and total mixed ration (TMR) compared to exclusively TMR-fed ones. In order to trace the type of animal feeding system, Prache and Theriez (1999) developed the traceability index, based on the carotenoids spectra data elaboration.…”
Section: Introductionmentioning
confidence: 67%
“…Cheese yellow index (b*) showed an average value of 20.0, higher than the average value of 11.5 observed by Carpino et al (2004) in Ragusano cheese produced by cattle fed on TMR plus pasture. Yellow index showed a decrease along grazing season ranging from 21.1 to 18.1 as average value of the two farms.…”
Section: Resultsmentioning
confidence: 88%